Dynamic failure mechanisms of granular boron carbide under multi-axial high-strain-rate loading. (December 2019) - Chauhan, Ankur; Sun, Xiangyu; Ramesh, Kaliat T.; Hemker, Kevin J.
Abstract: Boron carbide is an excellent protection material but it is also very brittle, and granular flow, triggered by progressive fracture during impact, greatly influences its ballistic performance. Transmission electron microscopy observations of samples recovered from controlled pressure-shear plate impact experiments have elucidated the extent to which local failure mechanisms accompany dynamic granular flow. These observations point to the interplay of quasiplasticity, the formation of nanoscale amorphous bands, cleavage and intragranular cracking. Association of these mechanisms with granular flow and identification of a critical velocity for the onset of amorphization provides a foundation for modeling and predicting armor performance. Graphical abstract: Unlabelled Image